INTEREST INCOME AND DEPOSIT MONEY BANKS (DMBs) PERFORMANCE IN NIGERIA - Russell Olukayode Christopher Somoye; Bamidele M. Ilo; Lateef Adewale Yunusa (Economic Review)
The role of deposit money banks (DMBs) as a critical component of the financial intermediary component of the financial systems for the benefit of their shareholders and the economy at large has become more pronounced in recent times. Banks help link both the surplus spending unit and the deficit spending unit for a fee which is interest income. Interest income is generated from the traditional activities of banks as a reward for their intermediation. This study thus, examined the impact of interest income on the performance of DMBs in Nigeria. The study employed data from the annual reports and accounts covering the period 2012-2017 of fifteen (15) selected interest charging DMBs out of the twenty-one (21) listed banks on the Nigerian Stock Exchange as on 31st December, 2018. The results obtained from the random effect model indicate that interest income and capital adequacy contribute and significantly drive the profitability of the Nigerian DMBs. The study therefore recommends that DMBs should maintain an adequate level of capital and a stable interest income through effective management of loans and advances in order to increase the income generated from lending and consequently improve their profitability for the benefit of their shareholders.